Log in to add a comment

## Answers

The Brainliest Answer!

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

LHS;

=> √1/cos²Ф +1/sin²Ф

=> √(sin²Ф+cos²Ф)/(sin²Фcos²Ф)

=> √1/(sin²Фcos²Ф)

=> 1/sinФcosФ

RHS;

=> tanФ+cotФ

=> sinФ/cosФ+cosФ/sinФ

=> (sin²Ф+cos²Ф)/sinФcosФ

=> 1/sinФcosФ

Thus LHS=RHS,

Hence Proved...

=> √1/cos²Ф +1/sin²Ф

=> √(sin²Ф+cos²Ф)/(sin²Фcos²Ф)

=> √1/(sin²Фcos²Ф)

=> 1/sinФcosФ

RHS;

=> tanФ+cotФ

=> sinФ/cosФ+cosФ/sinФ

=> (sin²Ф+cos²Ф)/sinФcosФ

=> 1/sinФcosФ

Thus LHS=RHS,

Hence Proved...

cosec^2Φ=1/sin^2Φ

adding these two we get sin^2Φ +cos^2Φ/sin^2Φ cos^2Φ

therefore the answer is 1/sinΦcosΦ

on the otherhand RHS is tanΦ+cotΦ=sinΦ/cosΦ+cosΦ/sinΦ=1/sinΦcosΦ